The buffering of a riverine carbonate system under the input of acid mine drainage: Example from a small karst watershed, southwest China - Huang, Jiangxun; Li, Qingguang; Wu, Pan; Wang, Shilu; Gu, Shangyi; Guo, Mingwei; Fu, Yong (Frontiers in Environmental Science, 2022)
In a karstic area affected by acid mine drainage (AMD), hydrochemical conditions, such as temperature, salinity, alkalinity, DIC, dissolved oxygen, and nutrients, may affect the buffering capacity of carbonate systems in freshwater systems. The resulting pH fluctuation is larger than that of a marine system. Therefore, this study focuses on the buffering of a riverine carbonate system under the input of AMD and discusses the variations in a series of buffering factors, including the Revelle factor, γDIC, γAlk βDIC, βAlk, ωDIC, and ωAlk. The results revealed that the Revelle factor could reflect the buffering process effectively; in addition, the maximum value of the Revelle factor appeared at pH=8.5. The data points for pH greater than this value indicated that the Huatan River had the ability to absorb atmospheric CO2 in spring. Conversely, the data for pH less than this value reflected the buffering of H+ during CO2 degassing in summer and autumn. In winter, the data were around the maximum value, indicating the weakest buffering capacity. At this time, the dynamics of the carbonate system caused the most sensitive response to pH. In addition, the maximum Revelle factor value did not always indicate the carbonate system had reached equilibrium; the presence of strong CO2 degassing was still a possibility. Under acidic conditions, as CO2(aq) increased, the absolute values of γDIC, βDIC, ωDIC, and γAlk increased accordingly, indicating the enhanced buffering capacity of H+ during CO2 degassing. Under the four Representative Concentration Pathways scenarios (RCPs) included in the IPCC’s fifth assessment report, the degassing rate of the Huatan River would decrease by 5%, 15%, 26%, or 48%, depending on the scenario. Even though the Huatan River revealed CO2 degassing characteristics in winter and spring under current conditions, it will eventually become a sink for atmospheric CO2 as atmospheric CO2 concentration increases. Therefore, the carbon sink effect in karst areas will become increasingly important.